Factors taken into account for the prescription and pharmaceutical promotion. medellín, colombia, 2011 (2012)
Cross-sectional study carried out in 2011 in a sample by convenience of 128 general practitioners and specialists from the city of Medellín (Colombia). A self-reported anonymous survey was made containing information sociodemographic, best advertising strategies employed by the pharmaceutical industry, criteria for medical prescription and usually consulted information source. The results showed that 57% of the participants were men, the median age was 35±11 years and two of every five were general practitioners. Best strategies of promotion pharmaceutical considered by practitioners were: invitations to congresses (86%) and promotion of samples (77%). On average, each practitioner received a monthly visit by visitor medical, and attendance at events sponsored by the pharmaceutical industry was 61% in the last year. Only 3% of participants take into account the recommendation of a visitor to prescribe, preferring the experience with the drug (92%), studies of effectiveness (91%) and inclusion in the clinical protocols (69%). The conclusion of this study is that despite the use of some promotional strategies for the pharmaceutical industry, its influence is not a determinant in prescription habits that are considered to be other criteria.